DAYA TERIMA DAN PENGETAHUAN CALON PENGANTIN (CATIN) WANITA SEBELUM DAN SESUDAH EDUKASI GIZI MENGGUNAKAN APLIKASI 1000 HPK BERBASIS ANDROID - Erni; Rosmida Marbun; Fajar Meirani (Balitbangda Provinsi Jambi, 2021)
The efforts to improve nutritional status for the human resources development must be started as early as possible, one of the things that can be done to improve nutrition status is the fulfillment of balanced nutrition in the period of 1000 first days of life (1000 HPK). This study aims to know the acceptability and the change of knowledge about 1000 HPK of brides at KUA Pesanggrahan District, South Jakarta by using the